2006
DOI: 10.1038/sj.jcbfm.9600325
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis for Estimating Binding Potential of the Peripheral Benzodiazepine Receptor with [11C]DAA1106

Abstract: [ 11 C]DAA1106 is a potent and selective ligand for the peripheral benzodiazepine receptor (PBR) with high affinity. It has been reported that the density of PBR is related to brain damage, so a reliable tracer method for the evaluation of PBR would be of use. We evaluated a quantification method of [ 11 C]DAA1106 binding in simulated data and human brain data. In the simulation study, the reliability of parameters estimated from the nonlinear least-squares (NLS) method, graphical analysis (GA), and multilinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…Among this class of ligands, [ 11 C]DAA1106 and [ 18 F] FEDAA1106 have been studied in monkeys and demonstrate high brain uptake and high ratios of specific to nonspecific binding Zhang et al, 2004). Studies in human with these ligands show high brain uptake, but displacement studies have not been performed to measure definitively the percentage of specific binding in human brain (Fujimura et al, 2006;Ikoma et al, 2007). Furthermore, [ 11 C]DAA1106 has been directly compared with [ 11 C](R)-PK11195 in rats under baseline conditions and after inflammation had been induced with neurotoxins (Venneti et al, 2007a;Venneti et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Among this class of ligands, [ 11 C]DAA1106 and [ 18 F] FEDAA1106 have been studied in monkeys and demonstrate high brain uptake and high ratios of specific to nonspecific binding Zhang et al, 2004). Studies in human with these ligands show high brain uptake, but displacement studies have not been performed to measure definitively the percentage of specific binding in human brain (Fujimura et al, 2006;Ikoma et al, 2007). Furthermore, [ 11 C]DAA1106 has been directly compared with [ 11 C](R)-PK11195 in rats under baseline conditions and after inflammation had been induced with neurotoxins (Venneti et al, 2007a;Venneti et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Among this class of ligands, [ 11 C]DAA1106 and [ 18 F]FEDAA1106 ( Fig. 1) have successfully imaged PBRs in human and nonhuman primates with high brain uptake and a high percentage of specific binding (Fujimura et al, 2006;Ikoma et al, 2007;Maeda et al, 2004;Zhang et al, 2003). We also synthesized aryloxyanilide-based PET ligands that have high affinity and selectivity for PBRs: [ 11 C]PBR01, [ 18 F]PBR06, and [ 11 C]PBR28 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies demonstrated that they had higher uptake and more specific binding in rodent and primate brains than 11 C-PK11195 (20)(21)(22). Now, 11 C-DAA1106 and 18 F-FEDAA1106 are being used to investigate PBR in the human brain at our facility to elucidate the relationship between PBR and brain diseases (25,26). Subsequently, 11 C-PBR28, an analog of 11 C-DAA1106, was developed to localize and quantify upregulated PBR associated with cerebral ischemia in rats (27).…”
mentioning
confidence: 99%